Outcome of Patients With Metastatic Lung Neuroendocrine Tumors Submitted to First Line Monotherapy With Somatostatin Analogs - Lenotti, Elisa; Alberti, Andrea; Spada, Francesca; Amoroso, Vito; Maisonneuve, Patrick; Grisanti, Salvatore; Baggi, Alice; Bianchi, Susanna; Fazio, Nicola; Berruti, Alfredo (Frontiers in Endocrinology, 2021)
Objective: Antiproliferative activity of somatostatin analogs (SSAs) has been demonstrated in digestive neuroendocrine tumors (NETs), but few data have been published in patients with pulmonary NETs. We therefore conducted a retrospective study to provide additional data on the outcome of patients with metastatic lung NETs submitted to front line SSAs. Research Design and Methods: patients with metastatic lung NET treated with first line SSA-monotherapy (octreotide or lanreotide) in two different reference Institutions were reviewed. Outcome measures were progression-free survival (PFS) overall survival (OS), overall response rate and safety. We also explored prognostic factors associated with PFS. Methods: The outcome of consecutive patients (pts) with metastatic lung NETs, who underwent first-line treatment with SSAs, recruited from 2014 on 2019 in 2 Italian reference Institutions, was retrospectively evaluated. Results: Thirty-one patients entered the study: 14 (45.2%) with typical and 17 (54.8%) atypical carcinoid. Six patients (19.4%) had a carcinoid syndrome. 60.0% of patients had Ki-67≤10%. Two (6.5%) patients obtained a partial response, 24 (77.4%) disease stabilization while 5 (16.1%) had progressive disease. Median progression free survival (PFS) was 28.6 months, median overall survival (OS) was not attained. Ki-67≤10%, typical carcinoid histotype and non-functioning disease, were associated with a non-significant PFS prolongation. PFS in patients with atypical carcinoids and in those with Ki-67 >10% was greater than 19 months. Conclusions: The long PFS and OS obtained in this case series suggest that SSAs could be effective as first line approach in the management of patients with progressive, metastatic pulmonary NET.